Opportunities, challenges and development areas of chartered accountants in the Fourth Industrial Revolution - Chené Brands; Claude-Hélène Mayer; Rudolf M. Oosthuizen (SA Journal of Human Resource Management)
Orientation: The Fourth Industrial Revolution (4IR) marks a period of tremendous technological progress, altering professions across industries, including chartered accountancy.